Thermally and optically stimulated luminescence : a simulation approach - Chen, R. (Reuven).; Pagonis, Vasilis (Chichester : John Wiley & Sons, 2011)
'The emphasis in the present book will be on results that one can get from simulations, which can add a new dimension to results from theoretical considerations mainly based on simplifying assumptions. Chapter 1 will introduce both techniques. Thermoluminescence, methods for evaluating trapping parameters, and additional phenomena of TL will be featured in chapters 2 to 4. Optically stimulated luminescence (OSL) will be discussed in chapter 5 and the next chapters will detail analytical and approximate expressions of dose dependence of TL and OSL and simulations of TL and OSL in dating and dosimetry procedures. Chapters 8 and 9 will detail the pre-dose (sensitization) effect and simultaneous measurements. Chapters 10 to 13 will focus on applications in medical physics, radiophotoluminescence, quantum-mechanical basis of TL and OSL and the exponential integral. The book will conclude with the appendix and the bibliography'--
Includes bibliographical references and indexes.
Keywords: Thermoluminescence; Thermoluminescence dosimetry; Optically stimulated luminescence dating